Disrupting Colonial Identity: Puerto Rican Subjectivities in Cultural Essays. - ESTEVES-WOLFF, CRISTINA (Centro Journal)
This article explores Puerto Rican cultural and political subjectivities in essays by Arcadio Díaz Quiñones, Rubén Ríos Ávila, and Frances Negrón-Muntaner as discursive spaces of disruption, exposing the island's lived experience as a process of negotiation with power and precariousness. My analysis considers methods of resistance condensed in particular allocutions -- la brega, "queerness," and jaibería -- used by a subject or community to negotiate its relationship to political, economic, cultural, and social paradigms dictated by a colonial status quo as a vehicle for surviving and prospering within a hostile system. I situate the tension between collective narratives propagated by dominant interests within Puerto Rican society and subsequent disruptive counter and alternative narratives as the locus of a convoluted identity that allows for shifting loyalties. Finally, these essays embody a vital dialogue between generations and sites of enunciation: the island and its diaspora.